Posterior segmente intraocular inflammation : guidelines - Forrester, John V.; Okada, Annabelle A.; Benezra, David (The Netherlands : Kugler Publications, 1998)
Thi is the second educational publication of the international Ocular Inflammation Society wich deals with one the most important aspects of ofphthalmology - posterior segment intraocular inflamtionPSII, or as it is more commonly terned, posterior uveitis.
1. Overview of posterior segment intraocular inflamation 2. Type of posterior segment intraocular inflamation 3. Management of posterior segment intraocular inflamation
Título en inglés
Keywords: RETINA; OJO